The complete mitochondrial genomes of two skipper genera (Lepidoptera: Hesperiidae) and their associated phylogenetic analysis - Han, Yuke (Sci Rep, 2018)
The systematic positions of two hesperiid genera, Apostictopterus and Barca (Lepidoptera: Hesperiidae), remain ambiguous. We sequenced and annotated the two mitogenomes of Apostictopterus fuliginosus and Barca bicolor and inferred the phylogenetic positions of the two genera within the Hesperiidae based on the available mitogenomes. The lengths of the two circular mitogenomes of A. fuliginosus and B. bicolor are 15,417 and 15,574 base pairs (bp), respectively. These two mitogenomes show similar AT skew, GC skew, codon usage and nucleotide bias of AT: the GC skew of the two species is negative, and the AT skew of A. fuliginosus is negative, while the AT skew of B. bicolor is slightly positive. The largest intergenic spacer is located at the same position between trnQ and ND2 in A. fuliginosus (73 bp) and B. bicolor (72 bp). Thirteen protein-coding genes (PCGs) start with ATN codons except for COI, which starts with CGA. The control regions of both mitogenomes possess a long tandem repeat, which is 30 bp long in A. fuliginosus, and 18 bp in B. bicolor. Bayesian inference and maximum likelihood methods were employed to infer the phylogenetic relationships, which suggested that A. fuliginosus and B. bicolor belong in the subfamily Hesperiinae.